Bruxism: Recognizing of Overlooked Contributing Factor in Recurrent Aphthous Stomatitis (A Case Report) - Putri, Andi Anggun M; Israyani, Israyani; Ikbal, Muhammad (Hasanuddin University, 2021)
Objective: This paper aims to describe bruxism as the contributingthe factor of RAS that needed an interdisciplinary treatment approach toachieve successful treatment.Methods: A 46-year-old male came to the Dental Hospital, Faculty ofDentistry, Universitas Hasanuddin with the complaints of mouth ulcers for2 weeks since it was bitten while he was sleeping. These complaints oftenrecur in the same area since about 10 years ago. He had seen the dentistseveral times, but there was no improvement. Clinical examinationrevealed two yellowish irregular ulcers accompanied with tooth indentationon the right lateral of the tongue and lower labial mucosa. We detectedbruxism from the patient history, clinical examination, and questionnaire evaluation. We assumed that bruxism was the main contributing factor inthis case. The management of oral ulcers included tooth grinding andprescribing Doxycycline oral rinses 100 mg three times a day. The patientwas also referred to prosthodontists and psychologists for management ofbruxism. Results: The patient felt complete improvement since routinely using a mouthguard and coping with his anxiety.Conclusion: Bruxism can play a role as a contributing factor in RAS.Recognizing and managing parafunctional habits is very important toachieve successful treatment in this case.